Adolescent–adult nonmetastatic Ewing sarcoma—Experience from a large developing country. Issue 9 (15th May 2021) - Bajpai, Jyoti; Panda, Goutam Santosh; Chandrasekharan, Arun; Bhargava, Prabhat; Srinivas, Sujay; Laskar, Siddhartha; Dandekar, Sonal; Mokal, Smruti; Rekhi, Bharat; Khanna, Nehal; Menon, Nandini; Patil, Vijay; et al.
Abstract: Background: Outcome and toxicity data in adolescent–adult Ewing sarcoma (AA‐ES) patients are sparse and merits exploration. Methods: Histopathologically confirmed, nonmetastatic AA‐ES patients, who received standard institutional combination chemotherapy regimen (Ewing's family of tumors‐2001 [EFT‐2001]) comprising of ifosfamide plus etoposide and vincristine, doxorubicin plus cyclophosphamide, lasting a total of 12 months between 2013 and 2018, were analyzed for treatment‐related toxicities, event‐free survival (EFS), and overall survival (OS). Results: There were 235 patients (primary safety cohort [PSC]) with median age of 23 (15–61) years; 159 (67.7%) were males, 155 (65.9%) had skeletal primary and 114 (48.5%) had extremity tumors. One hundred ninety‐six (83.4%) were treatment naïve (primary efficacy cohort [PEC]) and of these 119 (60.7%) had surgery. In PEC, at a median follow‐up of 36.4 (interquartile range [IQR] 20–55) months, estimated 3‐year EFS and OS were 67.3% (95% CI 60.3–75.1%) and 91.1% (95% CI 86.7–95.7%), respectively. Of these, 158 (80.6%) complying with intended treatment, at a median follow‐up of 39 (IQR 26–57) months had an estimated 3‐year EFS of 68.2% (95% CI 60.3–76.1%). In multivariable analysis, good prognostic factors included longer symptom(s) duration (HR 0.93, 95% CI 0.86–0.994), ≥99% necrosis (HR 0.30, 95% CI 0.11–0.77), and treatment completion (HR 0.32, 95% CI 0.14–0.74). Among PSC, grade 3–4 toxicities were febrile neutropenia (119, 50.6%), anemia (130, 55.3%), peripheral neuropathy (37, 15.7%), with three (1.3%) chemo‐toxic deaths. Conclusions: The outcomes of AA nonmetastatic ES patients treated with EFT‐2001 regimen were comparable to those reported by others, with acceptable toxicity. This regimen can be considered a standard of care in AA‐ES.